Powering Towards Operations Excellence at Kim Tiong - Loh, Geok Cheng Priscilla (2007)
Success in today's challenging and unpredictable global business environments is marked by the ability to push the boundaries of the operations to a greater height by speed, efficiency and effectiveness. A Small Medium Enterprise (SME) company, like us, Kim Tiong Enterprises continually questions the conventional ways of performances, and always on the look out to embrace fresh paradigms to redefine the operational perspectives and create new solutions that transcend the company into extraordinary.